Conjugated NH2‐Enhanced Cross‐Linked Polymer Anode for Lithium‐Ion Batteries with High Reversible Capacity and Superior Cycling Stability. Issue 7 (20th May 2019) - Zhong, Weihao; Li, Liuqing; Cheng, Ao; Li, Zhaopeng; Li, Zhenghui
Abstract : With a mass of heteroatom‐containing functional groups, organic electrodes have satisfactory capacities and some specific advantages compared with inorganic materials in lithium‐ion batteries, such as environmental friendliness, sustainability, and low cost. However, it is still challenging to explore novel organic materials incorporating simple production processwa, good electrolyte insolubility, high specific capacity, and long‐term cycling stability. Herein, a novel conjugated NH2 ‐enhanced polymer anode with rigid molecular framework by one‐step Friedel–Crafts cross‐linking of p ‐phenylenediamine is synthesized. It is surprising to find that the conjugated NH2 greatly enhances the Li + insertion reaction of benzene rings and endows cross‐linked p ‐phenylenediamine (C‐PDA) with high reversible Li storage capacity. Furthermore, C‐PDA exhibits a rigid network‐like molecular structure, which effectively suppresses the dissolution in electrolyte and improves the cyclability. When used as an electrode in a lithium‐ion battery, the initial discharge and charge capacities of C‐PDA are as high as 1190 and 720 mAh g −1, respectively, and it delivers a stable capacity of 1200 mAh g −1 after cycling 100 times at 0.1 A g −1 . Even cycling for 800 times at 1 A g −1, C‐PDA still retains a capacity of 454 mAh g −1, with a capacity retention of 89% ( C 800th / C max ). Abstract : Conjugated NH2 is found to be efficient to enhance the lithium storage performance of benzene rings. Based on this finding, a novel organic electrode, hyper‐cross‐linked p ‐phenylnediamine (C‐PDA) with conjugated NH2 is fabricated and exploited as the anode in a lithium‐ion battery, which presents high reversible capacity and long‐term stability upon repeated charge/discharge processes.